Evidence that plant K+ channel proteins have two different types of subunits. - Tang, H (1995)
Plant K+ channel proteins have been previously characterized as tetramers of membrane-spanning alpha subunit polypeptides. Recent studies have identified a 39-kD, hydrophilic polypeptide that is a structural component of purified animal K+ channel proteins. We have cloned and sequenced an Arabidopsis thaliana cDNA encoding a 38.4-kD polypeptide that has a sequence homologous to the animal K+ channel beta subunit. Southern and northern analyses indicate the presence of a gene encoding this cDNA in the Arabidopsis genome and that its transcription product is present in Arabidopsis cells. To our knowledge, this is the first report to document the presence of K+ channel beta subunits in plants.